The impact of macroeconomic variables towards saving deposits at Agrobank / Nor Fazillah Muhamad Tumiran - Muhamad Tumiran, Nor Fazillah (Faculty of Business and Management, 2010)
This study is measuring the impact of macroeconomic variables towards saving deposits at Agro bank within 10 years period beginning from 2000 until 2009. Data analysis for this study was done through Statistical Package for Social Science (SPSS) Program in order to analyze and interpret the findings. The main indicator towards measuring the impact of macroeconomic variables towards saving deposits at Agrobank is using the regression analysis. The regression analysis is comprises of 1) Coefficient of determination (R2), 2) F-Statistic, 3) Coefficients, and 4) T Statistic. The results of the study show the impact of macroeconomic variables towards saving deposits are different. This proves by the results from the SPSS program used. Overall, I can consider that most of the result gathered in this study is significant.